2006
DOI: 10.1007/s11060-006-9162-9
|View full text |Cite
|
Sign up to set email alerts
|

Levetiracetam therapy in patients with brain tumour and epilepsy

Abstract: Epilepsy is a common clinical problem in patients with brain tumours, strongly affecting patients' quality of life. Tumour-related seizures are often difficult to control, and the clinical picture is complicated by frequent interactions between antiepileptic drugs (AEDs) and antineoplastic agents. We studied the safety and efficacy of levetiracetam (LEV), a new AED with a different pharmacological profile from traditional anticonvulsants, in 19 patients (6 females; age range 28-70 years, mean 48 years) with su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 19 publications
0
39
0
Order By: Relevance
“…In a uncontrolled prospective study, LEV was shown to be well tolerated and provided a good seizure improvement in 17 patients with BTE (Usery, Michael et al, 2009). Further studies confirmed the good profile of LEV in BTE Rosati, Buttolo et al ;Maschio, Albani et al 2006;Newton, Goldlust et al 2006) and metastatic brain tumor epilepsy Newton, Dalton et al 2007). Several experts recommend use of LEV as first monotherapy in BTE Vecht and Wilms ;Vecht and van Breemen 2006;van Breemen, Rijsman et al 2009), although others still suggest valproic acid, lamotrigine and topiramate as first choice treatments (van Breemen, Wilms et al 2007).…”
Section: -5 Antiepileptic Pharmacotherapymentioning
confidence: 58%
“…In a uncontrolled prospective study, LEV was shown to be well tolerated and provided a good seizure improvement in 17 patients with BTE (Usery, Michael et al, 2009). Further studies confirmed the good profile of LEV in BTE Rosati, Buttolo et al ;Maschio, Albani et al 2006;Newton, Goldlust et al 2006) and metastatic brain tumor epilepsy Newton, Dalton et al 2007). Several experts recommend use of LEV as first monotherapy in BTE Vecht and Wilms ;Vecht and van Breemen 2006;van Breemen, Rijsman et al 2009), although others still suggest valproic acid, lamotrigine and topiramate as first choice treatments (van Breemen, Wilms et al 2007).…”
Section: -5 Antiepileptic Pharmacotherapymentioning
confidence: 58%
“…52 A large number of smaller studies have also shown levetiracetam to be well tolerated in brain tumor patients, with somnolence or other behavioral side effects being the most common adverse events, 31,37,40,41,55,64 with adverse effects being mostly reversible with dose reduction or displacement. 31,34,67 Levetiracetam demonstrated significantly fewer adverse effects than phenytoin when AED prophylaxis was given for supratentorial surgery, along with statistically equal efficacy (1% vs 4.3% early seizure incidence). 37 In contrast, patients given phenytoin were more likely to experience adverse effects than a seizure (18% vs 4%), and were much less likely to remain on the medication 1 year after surgery than with levetiracetam (26% vs 64%).…”
Section: The New Generation Of Antiepileptic Drugs: Levetiracetammentioning
confidence: 99%
“…Several antiepileptic agents have appeared over the past two decades that have shown efficacy and greater tolerability in patients with brain tumour-related epilepsy [88][89][90][91][92]. The side effect profile of the traditional antiepileptic medications such as phenobarbital, phenytoin, carbamazepine and valproic acid was such [93,94,5,95] that it seemed often to take precedence over the desire to reduce seizure activity [96].…”
Section: Antiepileptic Medical Managementmentioning
confidence: 99%